Different or Similar Choices: The Effect of Decision Framing on Variety Seeking in Travel Bundle Packages. (January 2018) - Kim, Jungkeun; Kim, Peter Beomcheol; Kim, Jae-Eun
This research investigates whether different ways of framing decisions influence travelers' variety-seeking tendencies in choosing bundled product options. Based on the literatures of bundling, variety-seeking, and the decision-framing effect, we empirically test whether travelers show higher variety-seeking in travel package decisions when the bundle package is selected from a combined decision rather than from two single decisions. We also examine whether this different variety-seeking tendency is influenced by travelers' preference for consistency. The results of six experimental studies support our main proposition, and the substantive theoretical and managerial implications of the findings are discussed.